RUSSIA AND CENTRAL EUROPE IN SYMBOLIC AND LITERARY GEOGRAPHY (IMAGOLOGICAL REMARKS) - Zelenka, Miloš (Porównania, 2012)
While examining mutual perception of Central Europe and Russia as it has changed against the background of the complex East-West relation, the paper employs the motives of the theory of communication and intercultural studies (C. Guillén, H. Dyserinck, D. H. Pageaux, D. Ďurišin, etc.) known as imagology. As a cultural crossroads and geographical area where the non-Slavonic West and the Slavonic East come into contact, Central Europe has always featured a changeable position of transitional centres and peripheries with the specific mingling of ethnics, cultures, religions and ideologies. The fact that it is situated between two powerful nations, such as Germany and Russia, has fundamentally influenced not only political but also aesthetical communication between the Slavonic peoples and the West, which has often been maintained through myths, i.e. fictional and subjective images to interpret the reality. The mutual converging or diverging of Russia and the West has resulted from the religious oscillation and "splitting" of Slavonic peoples (namely the West Slavs) who, despite adhering to Western religion and policies, have fostered awareness of tribal affinity with Russia. The strongest ties with Russia were thus maintained by small Slavonic nations living in the Hapsburg Empire, whereas the Russian interest in Europe was rather aimed at Germany, France or England, and Central European area was deemed to be a zone of transition employed by Tsarist Russia or the Soviet Union as political powers to pursue their goals in the West. In contrast to it, Central European nations, the Czechs not excluding, forged ties with Russia as the inspiring leader and symbol of Slavonic independence, the more so in times of troubles, national danger and political instability. Their expectations were based on the common belief that “non-European” Russia and its otherness would become democratised through following the local tradition and supporting Czech interests in the geopolitical confrontation with the non-Slavonic West. As it seems, the relation between Central Europe and Russia will remain the focus of permanent metacritical discourse even in the early 21st century and one can only cherish hope that it will be a model of harmonious coexistence, mutual understanding and respect.